2015
DOI: 10.1007/s11095-015-1658-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Based Nanogels Produced by Microfluidics-Facilitated Self-Assembly Improves the Safety Profile of the Cationic Host Defense Peptide Novicidin

Abstract: Formulation in nanogels could be a viable approach to improve the safety profile of host defence peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…One of the challenges in the formation of nanogels by such polymers is a control over the particle size, which requires fine-tuning of the polymer concentrations or environmental parameters such as temperature, pH, and ionic strength. A study by Nielsen and co-workers has demonstrated that these challenges can be addressed by utilizing a microfluidics-based approach [33]. Overall, the advances in polymer chemistry led to the exceptional diversity and control over the composition, architecture and functionality of crosslinked nanogels, which in turn provide more flexibility to tune their properties to comply with targeted biomedical applications.…”
Section: Nanogels: Characteristic Featuresmentioning
confidence: 99%
“…One of the challenges in the formation of nanogels by such polymers is a control over the particle size, which requires fine-tuning of the polymer concentrations or environmental parameters such as temperature, pH, and ionic strength. A study by Nielsen and co-workers has demonstrated that these challenges can be addressed by utilizing a microfluidics-based approach [33]. Overall, the advances in polymer chemistry led to the exceptional diversity and control over the composition, architecture and functionality of crosslinked nanogels, which in turn provide more flexibility to tune their properties to comply with targeted biomedical applications.…”
Section: Nanogels: Characteristic Featuresmentioning
confidence: 99%
“…The nanogels exhibited good colloidal stability under different ionic strength conditions and allowed complete release of the peptide over 14 days. Furthermore, self-assembly of novicidin with hyaluronic acid into nanogels significantly improved the safety profile at least five-fold and six-fold when tested in HUVECs and NIH 3T3 cells, respectively, while showing no loss of antimicrobial activity against E. coli and S. aureus [96]. Li et al explored the potential application of AMPs in wound healing, by developing a biodegradable poly(L-lactic acid)-Pluronic L35-poly(L-lactic acid) (PLLA-L35-PLLA) in situ gel-forming system [97].…”
Section: Pectin Nanoparticlesmentioning
confidence: 98%
“…Nanogel size can be readily tuned by adjusting flow rate, solvent polarity, polymer composition, and concentration . Nanogels manufactured by microfluidics can be scaled up to enable large‐scale production . Microfluidics has been recognized also to be an efficient method to produce long‐meter fibers, useful for many applications in regenerative medicine or for drug delivery purposes .…”
Section: Introductionmentioning
confidence: 99%
“…Cell entrapment into microdevices is one of the most appealing and useful tool for cell‐based therapy and tissue engineering . Except the employ of alginate or other polysaccharides able of an ion coordination or salt sensitive crosslinking, only other few reports are found in the literature describing the use of microfluidic devices without using chemical cross linkers . Covalent crosslinking reactions are usually employed to reinforce structure of fibers and to fix their shape .…”
Section: Introductionmentioning
confidence: 99%